The Role of the Activator Additives Introduction Method in the Cold Sintering Process of ZnO Ceramics: CSP/SPS Approach - Yurii D. Ivakin (MDPI AG, 2021)
The great prospects for introducing the cold sintering process (CSP) into industry determine the importance of finding approaches to reduce the processing time and mechanical pressure required to obtain dense ceramics using CSP. The introducing zinc acetate into the initial ZnO powder of methods, such as impregnation, thermovapor autoclave treatment (TVT), and direct injection of an aqueous solution into a die followed by cold sintering process using a spark plasma sintering unit, was studied. The effect of the introduction methods on the density and grain size of sintered ceramics was analyzed using SEM, dynamic light scattering, IR spectroscopy, and XRD. The impregnation method provides sintered samples with high relative density (over 0.90) and significant grain growth when sintered at 250 °C with a high heating rate of 100 °C/min, under a uniaxial pressure of 80 MPa in a vacuum, and a short isothermic dwell time (5 min). The TVT and aqueous solution direct injection methods showed lower relative densities (0.87 and 0.76, respectively) of CSP ZnO samples. Finally, the development of ideas about the processes occurring in an aqueous medium with CSP and TVT, which are subject to mechanical pressure, is presented.